Zivot Andrews Test for Structural Break: A Consideration of Government Expenditure in Nigeria from Pre to Post Sap Era - Okoli, Uju Victoria; Ezenwobi, Ngozi Florence; Onugha, Chinwendu Benedette (Social Science Research, 2024)
This study examines Government Expenditure in Nigeria in the light of Zivot Andrews test for structural break. The specific objectives of the study were to ascertain if structural breaks existed during the pre SAP, SAP and post SAP periods for economic growth and aggregate spending in Nigeria during the period under study with the aid of secondary macroeconomic data sourced from World Bank Development Indicators (WDI) covering a period of 1970 to 2023. The method of analysis employed was auto regressive distributed lag (ARDL) technique using government expenditure on transport, communication, health, education and utility sectors as independent variables independent variables and Gross Domestic Product as the dependent variable. From the results we observed, there were structural breaks both highest peaks and lowest peaks experienced during the pre SAP, SAP and post SAP periods for economic growth and aggregate spending in Nigeria. The study therefore recommends that the government should not only increase its expenditure in the key sectors of the economy but should do so in line with the needs for these infrastructural facilities so that the economy can attain infrastructural development.